CFD study and experimental validation of multiphase packed bed hydrodynamics in the context of Rolling Sea conditions - Motamed Dashliborun, Amir; Larachi, Faïçal (AIChE journal, 2019)
The necessity for a validated computational fluid dynamics (CFD)‐based model to deepen our understanding about the complex hydrodynamics of gas–liquid flows in oscillating porous media has driven this experimental and simulation work. A transient three‐dimensional Euler–Euler porous media CFD model using moving reference frame and sliding mesh techniques was applied to elucidate the dynamic features of gas–liquid flows of cocurrent downflow packed beds subject to tilts and oscillations reminiscent of sea conditions. Incorporation of capillary and mechanical dispersion forces besides interphase momentum exchange terms in the CFD model to achieve reliable predictions was evaluated with respect to experimental data acquired by capacitance wire‐mesh sensors and differential pressure transmitter. In the light of the validated CFD model, a detailed sensitivity analysis was performed to address the interrelations between hydrodynamic parameters, influence of fluid properties and packing size on the model predictions, and additional contribution of column oscillations on multiphase dynamics. © 2018 American Institute of Chemical Engineers AIChE J, 65: 385–397, 2019